Particulate pollution transport episodes from Eurasia to a remote region of northeast Mediterranean. (March 2016) - Triantafyllou, E.; Giamarelou, M.; Bossioli, E.; Zarmpas, P.; Theodosi, C.; Matsoukas, C.; Tombrou, M.; Mihalopoulos, N.; Biskos, G.
Abstract: Long-range transportation of air pollutants from industrial and urban environments can significantly affect the quality of the air in remote regions. In this study, we investigate episodes of particulate transport (PT) from Eurasia to the remote environment of Northeastern Mediterranean, i.e., the region of the North Aegean Sea (NAS), during the summer when the synoptic Etesian wind conditions prevail. A temporary monitoring station was set up at a remote region on the island of Lemnos, which is located at the center of the NAS at a distance of ca. 250 km from the continent. Measurements of the aerosol particle size distributions, the total number and mass concentrations, as well as the chemical composition of the particles were conducted from 27 August to 10 September 2011. During this period, the wind speeds were high (typically higher than 5.5 ms −1 ) with a direction that mostly ranged from north to northeast (68% frequency). Winds having direction ranging from northwest to south were less frequent (7% frequency), while the rest of the cases were characterized as calm (i.e., wind speeds less than 1 m s −1 ; 25% frequency). Seven PT episodes were observed during the sampling period. When the wind direction was northeastern we observed up to a six-fold increase in particle number concentration of nucleation mode, while the peak size of the particles decreased from 100 to 20 nm. Interestingly, the nucleation-mode particles grew from ca. 15 to 25 nm with rates of ca. 9.0 nm h −1, which are representative of polluted areas. Analysis of the chemical composition of particle samples collected on filters during the PT episodes shows that the concentration of sulfates and nitrates increased by ca. 60%, while the OC/EC ratio increased by ca. 22% compared to the rest of the sampling period. Back-trajectory analysis for the period during the episodes shows that the air masses arriving at the station passed over the greater Istanbul area and the Black Sea 9 to 12 h before reaching our station. These observations provide strong evidence that the air quality in the remote region of the NAS can be significantly affected by the transportation of particulate pollution during the summer period, having potentially important effects upon human health and climate in the region.